MANAJEMEN SISTEM PENDIDIKAN NASIONAL (Strategi dan Upaya menghadapi Tantangan Globalisasi melalui Pendidikan) - Asiyah Asiyah (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The management of national education is essentially an integral part  of the education management system and  process as a whole  in achieving national education and  development goals.  Government policies and  efforts are proposed by experts in addressing national education management issues. Implementation of basic  education seen from various aspects, politics, technical education, culture and professional, it is clear that the problem of basic educa- tion  management is not  a small  problem and  cannot be placed in a simple dichotomy: centralistic vs. decentralistic. A centralized education management system  has been shown to have made little progress in improving the quality of education in general. Even in certain cases, centralized management has resulted in the sterilization of creativity in edu- cational units  of various types and  levels of education. To overcome the stagnation in the field of education is required a new paradigm in the field of education.